Hubungan antara Berpikir Positif Dengan Harga Diri pada Lansia yang Tinggal di Panti Jompo di Bali - Andini, Ayu; Supriyadi, Supriyadi (Jurnal Psikologi Udayana, 2013)
Year by year, the amount of elderly who lives at nursing home in Bali are increasingly. Most of them be carried to nursing home by their families with a reason that they are not able to take care of their elderly at home. It makes that there is a lot of elderly think negatively about the decision to put them at nursing home. Negative thinking makes them have a low self esteem. According to it, this study aiming to see the relationship positive thinking and self esteem to the elderly. This study is a correlational study between 84 elders who lives at nursing home in Bali as a subject. Method of data collection in this study is using questionnaires. The variable of positive thinking is measured positive thinking questionnaire, and the variable of self esteem is measured by self esteem questionnaire. Both of them are already valid and reliable. Positive thinking questionnaire consist of 22 items which validity range from 0,259 to 0,935 and the coefficient reliability is 0,944. Self esteem questionnaire consist of 23 items which validity range from 0,282 to 0,938 and the coefficient reliability is 0,959. The result of nonparametric Kendall’s Tau show that there is a significant relationship between positive thinking and self esteem (r=0,422 ; p=0,000). It that can be concluded that variable of positive thinking can explain the variable of self esteem in 17,8%. It can explain that the hypothesis  which stating that there is a relationship between positive thinking and self esteem to the elderly who lives at nursing home in Bali can be accepted. The other things that can explain about the relationship between positive thinking and self esteem are because the elderly able to; (1)accept themselves and their condition, (2) adapt with their environment, (3) see themselves positively, (4) show their power, (5) show their competence.   Keyword : positive thinking, self esteem, elderly, and nursing home